2019
DOI: 10.1186/s40510-019-0299-4
|View full text |Cite
|
Sign up to set email alerts
|

A comparative assessment of clinical efficiency between premium heat-activated copper nickel-titanium and superelastic nickel-titanium archwires during initial orthodontic alignment in adolescents: a randomized clinical trial

Abstract: BackgroundTo compare the clinical efficiency of premium heat-activated copper nickel-titanium (Tanzo Cu-NiTi) and NT3 superelastic NiTi during initial orthodontic alignment.Subject and methodsA total of 50 patients were randomly allocated to 1 of 2 different archwire types (group 1, Tanzo Cu-NiTi; group 2, NT3 superelastic NiTi). Eligibility criteria included Class I or Class II malocclusion, moderate maxillary anterior crowding, and healthy periodontal condition. Impressions of the upper arches were taken bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…The heat treatments were effective in improving the fatigue resistance, especially upon the formation of R-phase. Atik et al [36] studied the clinical efficiency between premium heatactivated Ni-Ti and superelastic nickel-titanium archwires during the initial orthodontic alignment in adolescents. In conformity to their outcomes, there were no significant between-group differences in terms of alignment efficiency, arch width, and incisor inclination change.…”
Section: Discussionmentioning
confidence: 99%
“…The heat treatments were effective in improving the fatigue resistance, especially upon the formation of R-phase. Atik et al [36] studied the clinical efficiency between premium heatactivated Ni-Ti and superelastic nickel-titanium archwires during the initial orthodontic alignment in adolescents. In conformity to their outcomes, there were no significant between-group differences in terms of alignment efficiency, arch width, and incisor inclination change.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of self-ligating brackets, passive brackets minimize frictional resistance compared to active brackets, especially when NiTi and beta-titanium archwires are used [45]. Regarding the archwires, there is no difference in the effectiveness of dental alignment between the superelastic NiTi wires and the heat activated Cu-NiTi wires [46]. However, in low-friction mechanics such as self-ligating brackets, thermal archwires are preferred over superelastic ones in the early stages of fixed orthodontic treatment [47].…”
Section: Discussionmentioning
confidence: 99%
“…In line with our findings, Aydin et al [ 14 ] Gok et al [ 15 ] and Pandis et al [ 3 ] demonstrated that Cu-NiTi archwire did not have higher efficacy than NiTi archwire for leveling and alignment of the mandibular teeth. Also, Atik et al [ 6 ] compared Tanzo Cu-NiTi and NT3 super-elastic NiTi (SENT) archwires and found no significant difference between them in correction of crowding of the maxillary teeth. Similarly, Nabbat and Yassir [ 16 ] reported equal efficacy of heat-activated NiTi (HANT) archwire and SENT archwire for alignment of the teeth.…”
Section: Discussionmentioning
confidence: 99%
“…Following the introduction of NiTi archwires to orthodontics, different elements were added to this alloy to confer clinical advantages. Copper (Cu) is added to NiTi alloy to decrease the loading stress, and lead to more effective orthodontic tooth movement by provision of optimal force [ 6 ]. The Cu-NiTi archwire has thermo-elastic properties due to its phase transition depending on temperature [ 7 ].…”
Section: Introductionmentioning
confidence: 99%